Unusual metallo-β-lactamases may constitute a new subgroup in this family of enzymes - Hou, Chun-Feng D.; Phelan, Emer K.; Miraula, Manfredi; Ollis, David L.; Schenk, Gerhard; Mitić, Nataša (Scientific Research Publishing, 2014)
Metallo-β-lactamases (MBLs) are a family of Zn2+-dependent enzymes that have contributed strongly to the emergence and spread of antibiotic resistance. Novel members as well as variants of existing members of this family are discovered continuously, compounding their threat to global health care. MBLs are divided into three subgroups, i.e. B1, B2 and B3. The recent discovery of an unusual MBL from Serratia proteamaculans (SPR-1) suggests the presence of an additional subgroup, i.e. B4. A database search reveals that SPR-1 has only one homologue from Cronobacter sakazakii, CSA-1.These two MBLs have a unique active site and may employ a mechanism distinct from other MBLs, but reminiscent of some organophosphate-degrading hydrolases.
Keywords: Antibiotic Resistance; β-Lactam Antibiotics; Metallo-β-Lactamases; Sequence Homology; Serratia proteamaculans; Cronobacter sakazakii